2014
DOI: 10.1111/ppe.12113
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Mediterranean Diet during Pregnancy on Fetal Growth and Preterm Delivery: Results From a French Caribbean Mother–Child Cohort Study (TIMOUN)

Abstract: Background: Recent studies suggest that a Mediterranean dietary pattern during pregnancy may influence pregnancy outcomes. The aim of this study was to evaluate the effect of adherence to a Mediterranean diet (MD) during pregnancy on fetal growth restriction (FGR) and preterm delivery (PTD) in a French Caribbean island where the population is largely of African descent and presents dietary patterns similar to MD. Methods: Using data from the TIMOUN Mother-Child Cohort Study conducted in Guadeloupe (French West… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
90
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(96 citation statements)
references
References 34 publications
5
90
0
1
Order By: Relevance
“…Consistent with others, we did not observe an association between maternal diet quality and preterm birth (13,15,16,19), with the exception of 2 studies that showed a lower risk of preterm birth with greater adherence to the DASH diet (21) and a Mediterranean diet (18). The latter study was restricted to participants with low-risk pregnancies (i.e., no pre-existing health conditions, no complications during previous pregnancies, were nonsmokers, etc.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Consistent with others, we did not observe an association between maternal diet quality and preterm birth (13,15,16,19), with the exception of 2 studies that showed a lower risk of preterm birth with greater adherence to the DASH diet (21) and a Mediterranean diet (18). The latter study was restricted to participants with low-risk pregnancies (i.e., no pre-existing health conditions, no complications during previous pregnancies, were nonsmokers, etc.…”
Section: Discussionsupporting
confidence: 61%
“…), and the results may not be applicable to other populations of pregnant women (18). The intake of sweetened beverages was accounted for in the DASH diet (21) but less emphasized in other diet quality indexes (13,15,16,19,30). Earlier studies have shown that the intake of sweetened beverages during pregnancy is associated with an increased risk of preterm birth (47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a separate study in a cohort of pregnant Norwegian women, no association was found between the Mediterranean-style diet and preterm birth (6). In a retrospective study in women from a French Caribbean Mother-Child Cohort Study (TIMOUN), adherence to a Mediterranean-style diet was associated with a lower risk of preterm birth only in overweight and obese women (OR: 0.70; 95% CI: 0.60, 0.90) (29). With the use of a Mediterranean Diet Score and the Diet Quality Index, no association with preterm birth was found for either of the indices in the year before pregnancy in the National Birth Defects Prevention Study (7).…”
Section: Discussionmentioning
confidence: 91%
“…Dietary factors during pregnancy are very important for maternal health as well as for fetal growth [1,2]. Existing evidence has shown that an imbalanced maternal diet during pregnancy is associated with multiple adverse pregnancy outcomes, such as gestational diabetes mellitus (GDM), gestational hypertension, pre-eclampsia, fetal growth restriction, preterm birth, low birth weight, and macrosomia [1,2,3,4].…”
Section: Introductionmentioning
confidence: 99%